ANALISIS EFEKTIVITAS JALUR PEMBIAYAAN SYARIAH TERHADAP PRODUK DOMESTIK BRUTO USAHA MIKRO KECIL DAN MENENGAH DI INDONESIA DENGAN METODE VAR - Fajar Noverianto; Nirdukita Ratnawati (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2014)
This study aimstoseehow the financing linesofIslamic bankingtowards Gross Domestic Productof SMEs (Small and Medium Enterprises)inIndonesia. To getthe purposeofthis study, the analysis toolusedis aVectorAutoRegression(VAR). Some of thevariables usedin this researcharePDBSMEs, SBIS, profit and loss sharing, andFinance(FINC) the period 2009:1to 2013:12. The results ofthe analysisofthis study showedthat theGDPof SMEsrespondsis relativelyquickly, in the 5th periodon the development ofIslamic banking industry. In terms ofdonationsandthe influence ofseveralvariablesthatdeterminants ofGDPSMEsare SBIS, profit and loss sharing, however Islamic financevariablewith a value of24.11% VDis the largest contributortothe GDPof SMEs.